Meaning of Accounting at The Gandrung Sewu Festival (Ethnographic Study In Banyuwangi Society) - Shofyan Hadi (KUNKUN: Journal of Multidisciplinary Research, 2024)
This study aims to interpret and reflect on the meaning of the art and culture gandrung dance of Banyuwangi that we often encounter in the event Banyuwangi Festival every year in Banyuwangi. Gandrung dance is one of  original culture from     Blambangan, during an appearance gandrung dance presented in the form of song and dance to the accompaniment of music typical of the Java-Bali. As part of a community that community would be haven for this Gandrung dance community requires knowledge and accounting reports for next activity. This study is a qualitative study using ethnographic studies. Data obtained from informants who are the indigenous Banyuwangi society, through in depth interviews, documentation and direct observation. Based on the survey results revealed that purport accounting practices obtained by the informant showed that Banyuwangi society particularly those members of the community or community gandrung dance  attend  gandrung sewu this is a form of love in preserving cultural values ​​in Banyuwangi. Results obtained if a participant in the event merely as a means of preserving and ensuring the sustainability of a community or a community gandrung dance. Results reconstruction accounting concepts gandrung sewu in Banyuwangi society shows that gandrung Sewu is a form of accountability to the community or the community still preserve the culture and also a pride for the people of Banyuwangi particularly those participating in the event gandrung Sewu